2019
DOI: 10.1002/ecs2.2817
|View full text |Cite
|
Sign up to set email alerts
|

Carnivore space use shifts in response to seasonal resource availability

Abstract: Estimating spatial and temporal resource use and partitioning among carnivore species varies based on life history and is critical to understanding ecological relationships of sympatric carnivores and their prey. Temporal variation in food availability can have a substantial influence on distribution, foraging behavior, prey selection, and population dynamics of carnivores. We investigated shifts in space use of black bears (Ursus americanus), bobcats (Lynx rufus), coyotes (Canis latrans), and gray wolves (C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 122 publications
0
22
1
Order By: Relevance
“…Brown bears prey on ungulate neonates to varying extents depending on species, availability, and location 64 , 65 . We did not find a relationship between the presence of female elk during calving (spring) and bear range size on Afognak, which may reflect population-level opportunistic foraging of elk calves, as observed with black bears ( Ursus americanus ) and neonatal ungulates 52 , 66 , 67 . However, during the elk hunting period (fall), a decrease in the probability of elk occurrence resulted in an increase in bear range size on Afognak Island.…”
Section: Discussioncontrasting
confidence: 51%
“…Brown bears prey on ungulate neonates to varying extents depending on species, availability, and location 64 , 65 . We did not find a relationship between the presence of female elk during calving (spring) and bear range size on Afognak, which may reflect population-level opportunistic foraging of elk calves, as observed with black bears ( Ursus americanus ) and neonatal ungulates 52 , 66 , 67 . However, during the elk hunting period (fall), a decrease in the probability of elk occurrence resulted in an increase in bear range size on Afognak Island.…”
Section: Discussioncontrasting
confidence: 51%
“…Animal movements are reflective of their responses to biotic and abiotic conditions within their ranges (Svoboda et al., 2019). We observed that on average, coyotes moved ~6 km per day within their home ranges, comparable to more contemporary studies detailing coyote movements using GPS telemetry (Grubbs & Krausman, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…After emerging from hibernation, black bears consume substantial amounts of vegetation, but are unable to fully digest plant matter due to their simple digestive systems, making it difficult to meet their energetic needs on plant matter alone (Pritchard and Robbins 1990, Costello et al 2016, Herrero 2018. Later in spring, some black bears will take advantage of the availability of neonate ungulates, which are easier to digest than plant matter, but low in fat, which also makes regaining energy difficult (Pritchard and Robbins 1990, Barber-Meyer et al 2008, Bastille-Rousseau et al 2011, Schwartz et al 2014, Rayl et al 2018, Svoboda et al 2019.…”
Section: Introductionmentioning
confidence: 99%